AB0603 Serum uric acid as a predisposing factor of clinico- radiological severity of osteoarthritis knee. (23rd January 2014) - Srivastava, R. N.; Sanghi, D.; Mishra, A.; Sharma, A.; Natu, S. M.
Abstract : Background: Evidence suggests that uric acid involved in cartilage degeneration and other reported that it is a danger signal of increasing risk for OA through inflammasome activation and concluded that synovial uric acid is a marker of knee OA severity. feature of knee OA in Indian population. Objectives: Association of serum uric acid with clinico-radiologicalfeature of knee OA in Indian population. Methods: 180 ACR diagnosed OA knee patients as cases and equal number of controls were enrolled. Clinical OA outcome: pain, stiffness and functional disability were recorded by WOMAC & VAS. Radiological grading was done by KL grades. In addition, four radiological features- joint space width, osteophyte, subchondral sclerosis and tibio femoralalignment were also recorded separately. S. uric acid were measured by enzymatic Uricase-Peroxidase method. Results: KOA cases had significant higher BMI than controls in each group. In females, S uric acid were significantly higher in cases in comparison to controls but such association was not observed in males and in overall subjects. On analyzing uric acid with clinical features, pain was significantly associated with elevated S. uric acid in females; VAS pain alone in overall subjects but not in males. While studying the radiological features, an increasing KL grades was observed with increase in S. uric acid in overall and in both the genders separately. OA knee cases had significant higher BMI than controls in overall and in both the genders separately. In females, serum uric acid levels were significantly higher in cases in comparison to controls but such association was not observed in males and in overall subjects. Other biochemical variable like random blood sugar and total proteins were not significantly different between cases and controls in any category. On analyzing serum uric acid level with clinical features, pain (VAS and WOMAC) was significantly associated (p=0.02 and p=0.03) with elevated serum uric acid levels in females; VAS pain alone in overall study population (p=0.024) but not in males. While studying the radiological features, an increase severity of disease (increasing KL grades) was observed with increase in serum uric acid levels (KL grade 4 was 5.26 ± 1.1, KL grade 3 was 4.32 ± 0 .95 and KL grade 2 was 3.63 ± 0.95) in overall subjects and in both the genders separately. No significant association was observed for individual radiological features (IRF). Conclusions: Radiological severity and knee pain was found to be significantly associated with serum uric acid levels in overall subjects and in females in OA knee. Radiological severity (KL grade) and knee pain was found to be significantly associated with serum uric acid levels in overall subjects and in females in OA knee. Disclosure of Interest: None Declared